ENHANCING PROGRAM OUTCOME 11 ATTAINMENT THROUGH ASSESSMENT REVISIONS: A CONTINUOUS QUALITY IMPROVEMENT CASE STUDY - Anas Ibrahim; Nuraini Tutur; Md Rasul Mohamad Nor; Hazrina Ahmad; Juhaizad Ahmad (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
This paper presents the continuous quality improvement (CQI) implementation in outcome-based education (OBE) system at Civil Engineering Studies, College of Engineering, UiTM Cawangan Pulau Pinang. The CQI is key element of the OBE system and consistently practices safeguarding the quality of education program. The effective CQI process executed at a program level identified the issues of Program Outcome (PO) 11 (project management and finance) poor attainment for two semesters consecutively. Short term and long-term solutions were proposed and implemented by improving the assessment components (method and weightage) and PO-course re-mapping respectively. The amendment performed on assessment method was able to quickly turn around the situation with substantial improvements in term of cumulative percentage and percentage of student passing minimum requirement for PO11. The analysis of data proves that percentage of student achieved at least 50% of cumulative PO11 increased from 51% and 61% (before CQI) to 98% and 100% (after CQI) respectively. Both quantity and quality of PO improvement were achieved based on the database of students after the implementation of CQI. In conclusion, the effective CQI implementation play vital role in the quality assurance of OBE system.